The Effect of Cyberloafing on Employee Performance Through Employee Engagement at PT.ABC in Surabaya - Muhammad Rafi Achdiansyah; Khoirur Rozaq (Universitas Negeri Surabaya, 2026)
The purpose of this study is to examine and analyze the effect of cyberloafing on employee performance through employee engagement at Maritime Logistics Company in Surabaya. Previous studies have shown inconsistent findings regarding the relationship between cyberloafing, employee engagement, and employee performance, particularly in the context of state-owned or port service companies, indicating a research gap that needs further investigation. This research employs a quantitative approach using primary data collected through questionnaires distributed to employees of Maritime Logistics Company in Surabaya. The sampling technique used is saturated sampling, involving a total of 40 employees. Data analysis was conducted using Structural Equation Modeling (SEM) with the assistance of SmartPLS 3.2.9. The results of this study indicate that cyberloafing has a positive but insignificant effect on employee performance and a negative but insignificant effect on employee engagement. Meanwhile, employee engagement has a positive and significant effect on employee performance. Furthermore, employee engagement does not play a significant role in mediating the relationship between cyberloafing and employee performance. This study contributes to the literature by providing empirical evidence on the insignificant role of cyberloafing in influencing employee performance and engagement, as well as highlighting the limited mediating role of employee engagement in this relationship within the context of a port service company. Managerially, these findings imply that organizations should not solely focus on restricting cyberloafing behavior, but rather prioritize strategies to enhance employee engagement, as it has been proven to significantly improve employee performance.